PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BADUNG: The Effect of Work Discipline and Work Environment on Employee Performance with Work Motivation as a Mediating Variable in the Badung Regency Population and Civil Registration Office - Dewi, Ni Putu Agrin Cahya Purnama; Irwanti, Ni Ketut Dewi; Karta, Ni Luh Putu Agustini (Ganec Swara, 2025)
This study aims to analyze the effect of work discipline and work environment on employee performance with work motivation as a mediating variable at the Department of Population and Civil Registration of Badung Regency. This is a quantitative study with a causal research design. The sample consists of all civil servants at the institution, totaling 44 respondents, with data collected through questionnaires. Data were analyzed using path analysis. The results show that work discipline and work environment have a positive and significant effect on employee motivation. Work motivation significantly affects employee performance. Moreover, both work discipline and work environment significantly influence performance directly and indirectly through motivation. These findings highlight the importance of improving discipline, creating a conducive work environment, and enhancing employee motivation to improve overall performance